Volunteerism among Retirees: A Potential Resource for Community Development - Uttam Singh, Surjit Singh (2004)
Volunteerism was acknowledged by the United Nations by proclaiming the year 2001 as the Year of Volunteerism. There are thousands of retirees from the Premier and the Managerial and Professional Groups (PMP) of the Malaysian Public Service who, after the mandatory retirement at the age of 55, could contribute to the community in various ways considering that the longevity index in Malaysia presently stands at 71 for males and 76 for females. The study attempted to determine the involvement of the retirees in volunteerism, identify the relationship between their psycho-social variables towards altruism and volunteerism and to ascertain their inherent potential for volunteerism. There is no base- line research in Malaysia on retirees and this exploratory study could be significant to Government, Pensioners’ Associations, Yayasan SALAM, Senior Citizen Associations and various NGO’s for recruitment and social policy reviews. The sample was drawn from unequal clusters of randomly selected, one month for each year, for the period of 12 years (1989-2000). The list of addresses of 613 retirees was obtained from the Public Services Department (PSD) of Malaysia. A mailed survey was carried out with a sample of 576 retirees with a response rate of 261 (45.3%) of correctly completed questionnaires. The data analysis was carried out using descriptive and inferential statistics. The descriptive analysis elicited experiences and perceptions on motivating aspects, potential and preferences for volunteerism. The inferential statistics was used to compute difference of mean, relationship and mediating effect. Psycho-social variables (environment, life style, personality and resources), mediating variable (altruism) and dependent variable (volunteerism) were used for the analysis. T-tests, correlation and regression analysis were performed. The findings indicated that there were some differences between the western studies and the present study in the Malaysian context. There was significant correlation between personality and resources and volunteerism among the 52% volunteer-retirees. Altruism showed a mediating effect between psychosocial variables and volunteerism. The exploratory study provides a data-base to develop new strategies, further research and review the social policy to attract more retirees towards volunteerism. A model for the recruitment and sustaining of volunteers is suggested. In addition, a measurement of the contribution of volunteerism towards the Gross National Product is also proposed to add value to voluntary service.